“Must our wants / Find their supply in murder?”: Intersectional Social Conscience in Ann Yearsley’s “A Poem on the Inhumanity of the Slave Trade” - Andl-Beck, Boróka (FOCUS: Papers in English Literary and Cultural Studies, 2024)
For Ann Yearsley, issues like the abolition of the slave trade and the improvement of the working and living conditions of the English labouring classes were significant not only in her everyday life but also in her literary output. In the late eighteenth century, female writers had little chance to enter the public and literary discourse, but their voices were becoming gradually more audible, and the public literary and political platforms more accessible. Authors like Hannah More and Anna Laetitia Barbauld were at the forefront of the fight against slavery, but their backgrounds did not necessarily preordain their abolitionist positions—it was Yearsley whose social strata was the closest to the people whose liberation she advocated for. Rejecting the notion that the distance between Great Britain and its colonies where the slaves suffer most could be ignored by English authors and politicians due to geographical distance, Yearsley made a point that centuries later began to interest the likes of Judith Butler, who considered whether humans could ethically relate to human suffering at a distance. I would argue that Yearsley’s solidarity extended beyond the border of Britain and the continent of Europe precisely because she had experienced that proximity guarantees neither help nor compassion. Her general interest in politics, her radical, Protestant stance against exploitative practices, and her position as a woman intertwine and inform the rhetorical and poetical gestures present in her work “A Poem on the Inhumanity of the Slave Trade” (1788).